DESAIN PEMBELAJARAN GARIS DAN SUDUT DENGAN KONTEKS PAGAR BULUH DI KELAS VII - Widiawati W.; Dodi Marzal; Hariani Juwita (LP4MK STKIP PGRI Lubuklinggau, 2018)
The iemed of this study was to produce learning trajectories in helping students in learning lines and angles in the context of bamboo fences. The method used in this study was design research type validation studies by testing 6 students before involving 34 studentsof class VII MTs Negeri Jambat balo Pagaralam with by using Hypothetical Learning trajectory (HLT). Then the HLT was developed and a set of activities is applied to obtain a better understanding about how to develop the students understanding of line and angle material through three stages, namely preliminary design, the design experiment, and retrospective analysis. The research conducted produced learning trajectory which consisted of a series of learning processes in three activities, namely making bamboo fence, problem solving line material, and problem solving in angle material. The result of the research showed by using the bamboo fence context students understood the concepts in line and angle learning and students can solve problems related to the material lines dan angles in everyday life.